Between despair and spirit of life reflected in ernest hemingway's the old man and the sea (1952): a psychoanalytic criticism - Kurniati, Azizah, Dr. M. Thoyibi, M.S, Mauly Halwat Hikmat, Ph. D (2014)
The major problem of this study is how despair and spirit of life is reflected in Ernest Hemingway The Old Man and the Sea novel (1952). The objective of this study is to analyze the novel based on the structural elements and based on psychoanalytic criticism. The research uses qualitative research. The data of the research consists of primary data and secondary data. The primary data of the research is the The Old Man and the Sea novel and the secondary data of the research are other materials related of the study. Technique of data collecting is the library research the steps are: reading some books and articles, accessing internet, taking note important parts in both the primary data and secondary data, and arranging the data into several categories. In analyzing the data, the researcher employs descriptive qualitative method. The result of the study shows the following conclusion. Based on the psychoanalytic criticism analysis, it shows that The Old Man and the Sea novel illustrates a psychological phenomenon in which an individual has experienced the nature between despair and spirit of life desire. Santiago attempts to cover her conflict using his strength and courage, to end the cruelty of nature.